Budget-Balance, Fairness and Minimal Manipulability - Tommy Andersson; Lars-Gunnar Svensson; Lars Ehlers (Lund University, School of Economics and Management, Department of Economics, 2013)
A common real-life problem is to fairly allocate a number of indivisible objects and a fixed amount of money among a group of agents. Fairness requires that each agent weakly prefers his consumption bundle to any other agent's bundle. In this context, fairness is incompatible with budget-balance and non-manipulability (Green and Laffont, 1979). Our approach here is to weaken or abandon non-manipulability. We search for the rules which are minimally manipulable among all fair and budgetbalanced rules. First, we show for a given preference profile, all fair and budgetbalanced rules are either (all) manipulable or (all) non-manipulable. Hence, measures based on counting profiles where a rule is manipulable or considering a possible inclusion of profiles where rules are manipulable do not distinguish fair and budgetbalanced rules. Thus, a "finer" measure is needed. Our new concept compares two rules with respect to their degree of manipulability by counting for each profile the number of agents who can manipulate the rule. Second, we show that maximally linked fair allocation rules are the minimally (individually and coalitionally) manipulable fair and budget-balanced allocation rules according to our new concept. Such rules link any agent to the bundle of a pre-selected agent through a sequence of indifferences.
Keywords: C71; C78; D63; D71; D78; 330; Minimal manipulability; fairness; budget-balance; allocation rules